Involving Animal Models in Uterine Transplantation - Favre-Inhofer, Angeline; Carbonnel, Marie; Domert, Johanna; Cornet, Nathalie; Chastant, Sylvie; Coscas, Raphaël; Vialard, François; Gelin, Valérie; Galio, Laurent; Richard, Christophe; Trabelsi, Héla; Sandra, Olivier; et al. (Frontiers in Surgery, 2022)
Background: Absolute uterine factor infertility affects 0,2% women of childbearing age around the world. Uterine transplantation (UTx) is a promising solution for many of them since the first birth from UTx was described by the Swedish team in 2014. Success of Utx in humans has become possible after a systematic and meticulous approach involving years of research on animal models. To date, more than 80 UTx procedures have been performed worldwide and 30 children were born. Material and method: This review summarizes the research preparation conducted in animals before beginning uterine transplantation in humans. It focuses on the advantages and limits of each animal model, their place in surgical training and current contribution in research in order to improve UTx successes in humans. The different steps in the process of UTx have been analyzed: imaging, surgery, ischemia-reperfusion effects, rejection markers, immunosuppressive treatment, and pregnancy. Conclusion: Animal models have played an essential role in the implementation of UTx, which is a highly complex procedure. While respecting the 3R requirements (Replacement, Refinement, and Reduction), surgical training using large animal models such as notably ewes remain irreplaceable for teams wishing to initiate a UTx program. Furthermore, animal models are still mandatory in current research in order to improve the success rates of UTx in humans as well as to reduce the morbidity associated with this experimental infertility treatment.